2016
DOI: 10.3340/jkns.2016.59.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas with Rhabdoid or Papillary Components : Prognosis and Comparison with Anaplastic Meningiomas

Abstract: Papillary and rhabdoid meningiomas are pathologically World Health Organization (WHO) grade III. Any correlation between clinical prognosis and pathologic component is not clear. We analyzed the prognoses of patients with meningiomas with a rhabdoid or papillary component compared to those of patients with anaplastic meningiomas. From 1994 to June 2013, 14 anaplastic meningiomas, 6 meningiomas with a rhabdoid component, and 5 meningiomas with papillary component were pathologically diagnosed. We analyzed magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Importantly, this cluster also included meningiomas with concomitant anaplasia and patients with aggressive clinical courses. A previous study and meta‐analysis on rhabdoid meningiomas without anaplastic features suggested grading independent on morphology, 262 but such a thorough report does not exist for the papillary subtype, and non‐anaplastic cohorts are in general limited by small sample sizes 263,264 . Due to the highly varying but frequently aggressive clinical courses and risk of later anaplastic transformation, we argue that papillary and rhabdoid meningiomas, with or without concomitant anaplasia, should be addressed together with WHO grade 3 meningiomas.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Importantly, this cluster also included meningiomas with concomitant anaplasia and patients with aggressive clinical courses. A previous study and meta‐analysis on rhabdoid meningiomas without anaplastic features suggested grading independent on morphology, 262 but such a thorough report does not exist for the papillary subtype, and non‐anaplastic cohorts are in general limited by small sample sizes 263,264 . Due to the highly varying but frequently aggressive clinical courses and risk of later anaplastic transformation, we argue that papillary and rhabdoid meningiomas, with or without concomitant anaplasia, should be addressed together with WHO grade 3 meningiomas.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study and meta-analysis on rhabdoid meningiomas without anaplastic features suggested grading independent on morphology, 262 but such a thorough report does not exist for the papillary subtype, and non-anaplastic cohorts are in general limited by small sample sizes. 263,264 Due to the highly varying but frequently aggressive clinical courses and risk of later anaplastic transformation, we argue that papillary and rhabdoid meningiomas, with or without concomitant anaplasia, should be addressed together with WHO grade 3 meningiomas. It is necessary to increase knowledge of the clinical courses and anaplastic transformation of recurrences and compare to previous studies, including ours.…”
Section: Classification Of Meningiomamentioning
confidence: 99%
“…7,[33][34][35] Fingerlike protuberance and mushroom sign have also been reported by many scholars as the characteristic of malignant meningiomas. 5,26,36 The pathological basis is caused by tumor invasion of the adjacent dural surface, dura mater, arachnoid membrane, subarachnoid space, pia mater, and brain. 33,37 These are usually accompanied by an unclear and continuous tumor-brain interface.…”
Section: Discussionmentioning
confidence: 99%
“…Most meningiomas are benign, and have favorable outcomes with treatment using “wait and scan” or “stereotactic radiosurgery,” or “surgical resection” [ 2 ]. Anaplastic meningioma (World Health Organization [WHO] grade 3) consists of 1%–2% of all meningiomas and presents a particularly aggressive clinical course and a poor survival outcome [ 2 3 4 5 6 7 ]. In United States, population based study showed 5-year survival rate of patients with anaplastic meningiomas was 41.4% and factors associated with increased risk of death were older age, high comorbidity score, and subtotal resection [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a consensus in the literature that adjuvant irradiation is essential regardless of the extent of resection in patients with anaplastic meningioma [ 5 7 9 10 ]. However, due to the rarity of the anaplastic meningioma itself, there are few studies that have proven its prognostic value statistically [ 2 3 4 6 10 11 ].…”
Section: Introductionmentioning
confidence: 99%